Påverkan av ett strategiskt miljöbeslut - Brännström, Elin (2011)
Companies around the globe all have one thing in common; they are surrounded by individuals or groups of individuals that can influence the company in one way or another. These individuals and groups of individuals are called stakeholders. This study in concerned with the importance of a company’s awereness of and relationship with which stakeholders surround them. The fact that more companies show awareness of responsible conduct, in particular of the environment and social aspects of management may be a way to build a strong corporate image. It may also be a way to prevent a bad reputation. A company, whose actions do not comply with the frames in society at large could cause problems for the company. Such conflicts in the past have marked the history, based on pressure from stakeholders when companies neglect responsible actions. One example of such conflict, refered to as Brent Spar, took place in the 1990’s, between Shell and Greenpeace. This particular conflict has become a milestone in "corporate greening".